Collaboration on risk management: the governance of a non-potable water reuse scheme in London - Goodwin, Daniel; Jeffrey, Paul; Cook, H.; Raffin, M. (Elsevier, 2017)
Ageing water infrastructure and population growth, issues that are characteristic of megacities, are likely to exacerbate water supply deficits in London. To address this threat, wastewater reclamation and non-potable reuse can potentially close the supply-demand gap without impacting on environmental water bodies. There is a need to understand the types of challenges that diverse stakeholders face in relation to the governance of NPR schemes, and how those challenges might be addressed in a megacity context. A case study is used to explore these challenges for an operational sewer mining scheme in London, where reclaimed non-potable water is used for irrigation and toilet flushing at the site of the London 2012 Olympic Park. Through qualitative analysis of interview and document data, the results highlight that collaboration and learning opportunities are perceived as necessary to improve scheme governance. The findings indicate that formal and informal engagement activities centred on risk management can support the development of common understandings, build important inter-stakeholder relationships and help maintain trust. Non-potable reuse can contribute to the resilience of megacities through infrastructure diversification, but its feasibility will depend on the willingness of stakeholders to participate and continually negotiate new risk management practices.
Keywords: Non-potable reuse; Water reuse; Risk; Governance; Collaboration